2017
DOI: 10.1021/acsmedchemlett.7b00205
|View full text |Cite
|
Sign up to set email alerts
|

N-Acylbenzenesulfonamide Dihydro-1,3,4-oxadiazole Hybrids: Seeking Selectivity toward Carbonic Anhydrase Isoforms

Abstract: A series of N-acylbenzenesulfonamide dihydro-1,3,4-oxadiazole hybrids (EMAC8000a–m) was designed and synthesized with the aim to target tumor associated carbonic anhydrase (hCA) isoforms IX and XII. Most of the compounds were selective inhibitors of the tumor associated hCA XII. Moreover, resolution of EMAC8000d racemic mixture led to the isolation of the levorotatory eutomer exhibiting an increase of hCA XII inhibition potency and selectivity with respect to hCA II. Computational studies corroborated these da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…In case of hCA XII, the presence of dihalogens was beneficial, following the order 2,4-di-F > 2.4-di-Cl. Final- Based on their previous observations [278][279][280][281], Distinto et al [282] designed a library of 4-[(3-methyl-4-aryl-2,3-dihydro-1,3-thiazol-2-ylidene)amino] benzene-1-sulphonamides and synthesized in order to evaluate the effect of substituents in positions 3 and 4 of the dihydrothiazole ring on the inhibitory potency and selectivity toward human carbonic anhydrase isoforms I, II, IX, and XII. The study revealed that in accordance with their previous observations for compounds with similar structure, none of the synthesized compounds was active against hCA I isoform.…”
Section: Thiazole Derivatives As Carbonic Anhydrase Inhibitorsmentioning
confidence: 99%
“…In case of hCA XII, the presence of dihalogens was beneficial, following the order 2,4-di-F > 2.4-di-Cl. Final- Based on their previous observations [278][279][280][281], Distinto et al [282] designed a library of 4-[(3-methyl-4-aryl-2,3-dihydro-1,3-thiazol-2-ylidene)amino] benzene-1-sulphonamides and synthesized in order to evaluate the effect of substituents in positions 3 and 4 of the dihydrothiazole ring on the inhibitory potency and selectivity toward human carbonic anhydrase isoforms I, II, IX, and XII. The study revealed that in accordance with their previous observations for compounds with similar structure, none of the synthesized compounds was active against hCA I isoform.…”
Section: Thiazole Derivatives As Carbonic Anhydrase Inhibitorsmentioning
confidence: 99%
“…In this respect, the design of new psoralen derivatives as hCA IX and XII inhibitors could be advantageous and may lead to the identification of multitarget agents since other cancer related enzymes and pathways could also be hit by such derivatives. 6,7,9,14,15,29,30 Pursuing on our efforts in the design and synthesis of hCA inhibitors, 31,32 we have designed and synthesized a small library of coumarin (EMAC10151 A-D) and psoralen (EMAC10152 A-D) derivatives with the aim to target the hCA IX and XII isoforms. To achieve a deeper insight in the inhibitory potential of such derivatives, we have also synthesized EMAC10152 A-D and the corresponding benzenesulfonamide hybrids EMAC10153 A-D.…”
mentioning
confidence: 99%
“…33,34 The previously validated QMPL 35 protocol was applied. 32 Both coumarin derivatives have been prepared considering the possibility that the coumarin moiety can be hydrolyzed by the Zn 2+ activated water molecule of the enzyme cavity, which acts as a very potent nucleophile. 33 Therefore, the compounds were ionized at pH 7.4.…”
mentioning
confidence: 99%
“…Acetazolamide (5-acetamido-1,3,4-thiadiazole-2-sulphonamide) is known for its pan-isoform CA inhibitory profile which is considered a source of the plethora of side effects associated with this classical CA inhibitory drug 26 . Although potent and isoform-selective N-acyl sulphonamide CA inhibitors have been reported 27 , elsulfavirine itself demonstrated rather weak inhibition across the entire hCA panel, in the range of single-to double-digit micromolar concentrations with virtually no inhibition of hCA III and IV isoforms. To our delight, however, the primary sulphonamide VM1500A showed a much more effective inhibitory profile.…”
Section: Resultsmentioning
confidence: 94%